2014
DOI: 10.1056/nejmicm1305786
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Labialis and Facial-Nerve Paralysis

Abstract: images in clinical medicineT h e ne w e ngl a nd jou r na l o f m e dicine n engl j med 370;11 nejm.org march 13, 2014 1048A 65-year-old woman presented to the emergency department with odynophagia, facial edema, and perioral swelling with crusting blisters containing clear fluid (Panel A). One week earlier, she had completed one cycle of treatment with rituximab and bendamustine for chronic lymphocytic leukemia. In the emergency department, treatment with intravenous acyclovir was started for a clinical diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…1D) cranial neuropathy, cluster headache, and psychosis are possible, but rarely occur [4]. In a literature review, only a few cases of cranial neuropathy associated with HL have been reported, even there were no reports of CNS vasculitis due to invasion of HL [5][6][7]. Umehara et al ( 2012) reported a patient who developed trigeminal neuropathy after typical HL infection despite the negative result of CSF HSV PCR, which was similar to our case [5].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…1D) cranial neuropathy, cluster headache, and psychosis are possible, but rarely occur [4]. In a literature review, only a few cases of cranial neuropathy associated with HL have been reported, even there were no reports of CNS vasculitis due to invasion of HL [5][6][7]. Umehara et al ( 2012) reported a patient who developed trigeminal neuropathy after typical HL infection despite the negative result of CSF HSV PCR, which was similar to our case [5].…”
Section: Discussionsupporting
confidence: 80%
“…A previous study found various time intervals (12-27 days) between the onset of facial paralysis in Ramsay Hunt syndrome and the detection of brainstem involvement on brain MRI [10]. Moreover, it has been reported that patients experience worsening or progressive neurological deficits several weeks after the onset of facial paralysis [6]. Indeed, our patient developed sensory disturbance one week after the onset of HL.…”
Section: Discussionmentioning
confidence: 47%